2018
DOI: 10.1016/j.fertnstert.2017.11.018
|View full text |Cite
|
Sign up to set email alerts
|

Oocyte vitrification versus ovarian cortex transplantation in fertility preservation for adult women undergoing gonadotoxic treatments: a prospective cohort study

Abstract: Although we observed a trend toward higher LBR after OV, OCT is a very effective method to preserve fertility, allows for natural pregnancy, and restores ovarian function. In clinical scenarios where OV is not feasible, OCT remains the FP technique of choice and should no longer be considered experimental.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
129
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(134 citation statements)
references
References 31 publications
3
129
0
2
Order By: Relevance
“…In the present study, breast cancer and hematological malignancies constitute the most common oncological indications for fertility preservation, which is in accordance with the existing studies . A recent report on fertility preservation for adult women in Spain showed that breast cancer and hematological malignancies accounted for 60.3% and 21.4% of indications for oocyte cryopreservation, respectively, while accounted for 53.9% and 29.6% for ovarian tissue cryopreservation.…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, breast cancer and hematological malignancies constitute the most common oncological indications for fertility preservation, which is in accordance with the existing studies . A recent report on fertility preservation for adult women in Spain showed that breast cancer and hematological malignancies accounted for 60.3% and 21.4% of indications for oocyte cryopreservation, respectively, while accounted for 53.9% and 29.6% for ovarian tissue cryopreservation.…”
Section: Discussionsupporting
confidence: 91%
“…The efficacy of re‐transplantation of ovarian tissue compared with the use of vitrified oocytes has been reported in a previous study . Although a trend toward higher pregnancy and live birth rate was observed in 49 women who thawed oocytes vs 44 women after re‐transplantation (risk ratio [RR] 1.31, 95% CI .90‐1.92; RR 1.39, 95% CI .95‐2.03, respectively), it did not reach statistical significance.…”
Section: Discussionmentioning
confidence: 83%
“…However, in the vast majority of cancer patients, only 1 round of stimulation will be possible, and the number of oocytes retrieved has been found to be negatively correlated with age, but not with the type of cancer . Although oocyte/embryo vitrification is currently used routinely for young women requiring FP, the evidence regarding outcomes of IVF for cancer patients who have returned to use their stored oocytes, is scarce. The hitherto largest study, counting a cohort of 80 cancer patients, recently reported a cumulative live birth rate in young cancer patients (≤35 years) of only around 40%, whereas the percentage was markedly higher (around 70%) in the age‐matched group of elective freezers .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, oocyte vitrification is only now being implemented as a standard procedure in Danish fertility clinics, and cryopreservation of embryos is still considered the most established and reliable procedure in many centers. The superiority of oocyte vitrification also needs to be proven in the context of OTC, and so far, only 1 study by Diaz‐Garcia et al, have compared the efficacy of oocyte vitrification with that of OTC in a single‐center setting. Diaz‐Garcia et al found a trend toward higher clinical pregnancy rates and live birth rates after oocyte vitrification compared with OTC in breast cancer patients undergoing FP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation